ENGAGING TEACHING MEDIA OF EDUCAPLAY AND POWERPOINT TO IMPROVE READING AND LISTENING SKILLS - zulhijah anugrah saputra (LP3MKIL, 2025)
This study aims to examine the effectiveness of website-based quiz media in improving reading and listening skills of first-semester students of the English Education Study Program, PGRI Silampari University. The quiz media conducted through the website is designed to combine visual and interactive elements to create a more engaging learning experience. The results showed that 80% of students felt that this method was effective in improving reading skills, while 60% reported an improvement in listening skills. In addition, the majority of students stated that quizzes helped them understand weaknesses, increase motivation to study, and build confidence. This study concludes that interactive game-based quizzes are effective and can be useful learning strategies. Further research is needed to test the effectiveness of this medium against other language skills and on a wider scale.